Olfactory Disturbance Screening with the Odor Stick Identification Test (OSIT-J) in Executive Checkups - Saito, Sachiko; Tsukatani, Toshiaki; Kobayakawa, Tatsu; Miwa, Takaki; Furukawa, Mitsuru; Shiga, Hideaki; Deguchi, Yuichi; Kinoshita, Yayoi (Nippon Jibi Inkoka Gakkai Kaiho, 2007)
The odor stick identification test for Japanese (OSIT-J) has been shown to be useful for detecting and evaluating olfactory disturbances in Japanese people. We studied the usefulness of OSIT-J in screening for olfactory disturbances in 83 Japanese participants (49 male, 34 female) participating in an executive checkup at NTT West Kanazawa Hospital in Japan. The olfactory ability was self-reported on a grade scale. Olfactory function was then evaluated with a three-odors OSIT-J (rose, curry and sweaty socks). Participants with low self-reported olfactory ability or less-than-full scores in the three-odor test were evaluated with an additional 10 odors of OSIT-J. Eight or less points are considered to be lower than average in the 13-odor test of OSIT-J (Saito S, et al.). Eleven of the 83 participants had low self-reported olfactory ability. Four participants with a full score in the three odors test with low self-reported olfactory ability scored more than eight points in the 13-odor test. Thirty-eight participants scored less than three points in the three-odor test. Seven of 29 participants with two points in the three-odor test scored eight or less in the 13-odor test. In the 29 participants, subjects with low self-reported olfactory ability scored significantly lower scores than those without a low self-reported olfactory ability in the 13-odor test. The self-reported olfactory ability was not related to the score in the 13-odor test in the nine participants with one point or less in the three-odor test. Males scored significantly lower scores than females in the three-odor test. However, gender was not significantly related to the rate of olfactory disability estimated based on the 13-odor test. Use of a three-odor OSIT-J along with a self-administered questionnaire pertaining to olfactory disability is useful for olfactory disturbance screening during executive health checkups.